Social Capital in Temporary Inter-organizational Projects: A Third Sector Perspective - Tondolo, Rosana da Rosa portella; Bitencourt, Claudia Cristina; Gonçalves Tondolo, Vilmar Antonio (Desenvolvimento em Questão, 2015)
Social Capital emerges from the relationship among actors in several kinds of activities. Temporary inter-organizational project is one of those activities. Regarding these projects, social capital has the hole of being a way to nonprofit organizations access resources. In this context, these study aims to propose dimensions and categories of analysis to investigate social capital in the context of temporary inter-organizational projects in the Brazilian Third Sector. In order to achieve this goal we developed a literature review covering the main international journals of management field. As main results we may highlight the proposal of to consider mobilization as an important dimension in the study of social capital. Additionally, we regard as central to understand resources mobilization in the development of temporary inter-organizational projects in the third sector.